The Routledge Handbook of Sustainable Cities and Landscapes in the Pacific Rim. - Yang, Yizhao; Taufen, Anne. (Milton : Taylor & Francis Group, 2022)
This handbook addresses a growing list of challenges faced by regions and cities in the Pacific Rim, drawing connections around the what, why, and how questions that are fundamental to sustainable development policies and planning practices.
57 Engaged scholarship and co-production: the role of higher education institutions in urban sustainability - A Pacific Rim perspective -- 58 Structural erasure of Japanese Americans in Pre- WWII Tacoma, WA: working to imagine alternative futures -- 59 Chicana neighborhood activism: gender, race, and sustainability -- 60 Governing urban integration in china's land expropriation-induced resettlement neighborhoods: a Shanghai case study -- 61 Evaluating the United Nations Habitat guiding principles for urban-rural linkages: a case study of Chengdu -- 62 The co-production of risk knowledge: initiatives emerging from super Typhoon Haiyan -- 63 An Indigenous Feminist lens: dismantling the settler-colonial narratives of place- based knowledges in a climate justice world -- 64 Making sense of an emergent crisis: the case of the pandemic urbanism symposium -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books